From Traits to Intentions : How Personality Shapes Social Entrepreneurship in Tourism - Sunayana; Khan, Shadab Mohd; Naushad, Mohammad; Siddiqui, Taufeeque Ahmad (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study examined how the Big Five personality traits influenced social entrepreneurial intentions among tourism entrepreneurs through three mediators—empathy, moral obligation, and social entrepreneurial self-efficacy (SESE). It explored two pathways: embedding social goals in existing ventures (IVSI) and creating new social enterprises (NSVI). Methodology : Data from 324 entrepreneurs with at least one year of business experience were analyzed using partial least squares structural equation modeling (PLS-SEM) to assess measurement validity, structural relationships, and predictive power. Findings : Openness, agreeableness, extraversion, and conscientiousness positively fostered empathy, moral obligation, and SESE, while neuroticism exerted negative effects. These mediators significantly predicted IVSI and NSVI. SESE was the strongest predictor, whereas empathy and moral obligation were more influential for NSVI. The model showed strong explanatory power. Practical Implications : The results emphasized personality-based mentoring, self-efficacy training, and supportive policies to strengthen hybrid models, aligning economic viability with community impact. Originality : This study advances the literature by integrating personality traits (distal factors) with empathy, moral obligation, and SESE (proximal factors) into a dual-path model of social entrepreneurial intention in tourism. By differentiating between embedding social objectives in existing businesses and creating new ventures, it offers a nuanced understanding of how incumbent entrepreneurs pursue social goals, contributing both theoretical depth and practical relevance to the field of tourism social entrepreneurship.